International trade in practice of enterprises activity - Burinskienė, Aurelija (Business, Management and Economics Engineering, 2010)
Nowadays importance of international trade is rising; new perspectives for enterprises to sell products at international markets are more significant.In the article theoretical and practical aspects of international trade development are analysed; European Union manufacturing and trade enterprises are compared; practice of manufacturing and trade enterprises activity for development of international trade are presented. The study results show that European Union manufacturing enterprises are more active in international trade than trade enterprises. Also research shows that within manufacturing enterprises Denmark and Luxembourg enterprises are the most active in selling products abroad and in using traditional and online international trade development methods. Tarptautinė prekyba įmonių veiklos praktikoje Article in Lithuanian.